Yield and economics of mustard + chickpea intercropping system under cropping systems and nutrient management practices in rainfed condition - Sasmita Tripathy; S.L. Meena; Shiva Dhar; Sachin Singh (Annals of Agricultural Research, 2023)
A field experiment was conducted at the Indian Agricultural Research Institute, New Delhi, during the rabi seasons of 2021-2023 to identify the most suitable cropping system, row ratio, and nutrient management practices for mustard + chickpea intercropping. Although the individual crop yields of mustard and chickpea were highest in the sole cropping system, the intercropping system achieved the highest overall yield in terms of mustard equivalent yield for the mustard + chickpea 5:2 row ratio. The plots treated with a combination of organic manures and microbial consortia, specifically 20 kg nitrogen through farmyard manure + leaf manure + microbial consortia, resulted in the highest yields for both mustard and chickpea. Additionally, this treatment gave the highest gross returns, net returns, and benefit-cost ratio. Analysis of intercropping indices indicated that the mustard + chickpea 2:5 row ratio, when treated with organic manures and microbial consortia, demonstrated the highest intercropping advantage.